1996
DOI: 10.1007/bf02284791
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine hydroxylase, neuropeptide Y, substance P, calcitonin gene-related peptide and vasoactive intestinal peptide in nerves of rat periovarian adipose tissue: an immunohistochemical and ultrastructural investigation

Abstract: Rat periovarian adipose tissue contains unilocular adipocytes and some multilocular adipocytes that, following acclimation to cold, become more numerous and give rise to periovarian brown fat areas. We studied the occurrence and distribution of tyrosine hydroxylase, neuropeptide Y, substance P, calcitonin gene-related peptide, vasoactive intestinal peptide, methionine enkephalin, neurotensin, galanin, and cholecystokinin 9-20 in the nerves of rat periovarian tissue maintained at 20 degrees C (control rats), ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 40 publications
6
91
0
Order By: Relevance
“…Still, this finding did not gain wide acceptance or interest compared with that occurring now for brite/beige cells. At about the same time (1992), however, in a particularly thorough study, Cousin et al 17 in laboratory rats found both mRNA and protein for UCP-1 in several WAT depots (mesenteric, epididymal, retroperitoneal and inguinal) that was especially striking in periovarian WAT (which can possess some bona fide brown adipocytes; for example, see Giordano et al 18 ). As with BAT, cold exposure or β-adrenoceptor agonist treatment exacerbated the UCP-1 in these WAT depots.…”
Section: Methodsmentioning
confidence: 96%
“…Still, this finding did not gain wide acceptance or interest compared with that occurring now for brite/beige cells. At about the same time (1992), however, in a particularly thorough study, Cousin et al 17 in laboratory rats found both mRNA and protein for UCP-1 in several WAT depots (mesenteric, epididymal, retroperitoneal and inguinal) that was especially striking in periovarian WAT (which can possess some bona fide brown adipocytes; for example, see Giordano et al 18 ). As with BAT, cold exposure or β-adrenoceptor agonist treatment exacerbated the UCP-1 in these WAT depots.…”
Section: Methodsmentioning
confidence: 96%
“…White-to-brown transdifferentiation is essential to meet increased heat production requirements during chronic cold exposure. Cold exposure activates BAT by acting on the sympathetic nervous fibres that directly innervate brown adipocytes at the parenchymal level (36,37,38,39); chronic cold exposure results in branching of noradrenergic parenchymal fibres, significantly increasing BAT sympathetic innervation, a phenomenon that appears to be closely related to white-to-brown transdifferentiation (40,41). b3-adrenoceptors (AR) are specifically expressed by brown adipocytes.…”
Section: White-brown Plasticitymentioning
confidence: 99%
“…The capillary network is more dense in BAT and adrenergic fibres can be found both in WAT and in BAT, but their density is higher in BAT (18)(19)(20)(21)(22)(23)(24) .…”
Section: Adipose Tissuesmentioning
confidence: 99%